Ekowisata sebagai Bentuk Adaptasi Masyarakat Liang Ndara pada Pariwisata - Deni Alfian MBA (Universitas Andalas, 2020)
Tourism is continuing on growing to become one of the world most powerful economics powers and the main mover of the country’s economic system. Unfortunately, one the other hand, tourism can also promote harmful effects on social culture and environment. Therefore, it is necessary to develop a sustainable tourism strategy. Ecotourism as an alternative sustainable tourism that offers not only economic benefit but also nature preservation. This research focuses on the local’s adjustment towards the global tourism culture. This research which took place at Liang Ndara ecotourism village is meant to answer two main questions of firstly, how the locals adapt to the tourism phenomenon which situated in Labuan Bajo, NTT. Secondly, how they managed to succeed the adaptation process. In order to answer these questions, this research was conducted in qualitative methodology. This paper argues that the locals of Liang Ndara was able to adapt to the new realm of tourism, of ecotourism. They were capable of managing the financial benefit as well as the nature and ecology preservation. The most essential factors of the success was the sensitivity towards the change that is taken place in their surroundings. In addition to the sensitivity factor, there was a role model for the locals who developed the ecotourism. Moreover, it was the openness to build the network with different parties especially NGO that support the ecotourism which determined their success.